The Use of Sketch Word Strategy in Teaching Vocabulary - Samhudi (Medan Resource Center, 2021)
This research was aimed to find out whether using sketch word strategy was effective in teaching vocabulary. In this case, the researcher used quantitative data approach by using experimental design. There were two classes at seventh grade of SMPN 3 Nisam North Aceh as the sample of this research. There were class VII/1 as experimental consist of 24 students and VII/3 as control group consist of 22 students. In experimental group, the researcher used skecth word strategy in teaching vocabulary. After teaching learning process for three meetings, the researcher gave post-test. The result was shown that the students’ achievement in experimental group was higher than control group. It was proved by the average score from pre-test of experimental group was 64,5 and control group was 53,04. Furthermore, the result of post-test of experimental group was 83,5 and control group was 69,86. It could be concluded that using sketch word effective in teaching vocabulary.